To solve the quadratic equation \( x^2 - 6x - 16 = 0 \) using the quadratic formula, we use the formula:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
In this equation, \( a = 1 \), \( b = -6 \), and \( c = -16 \).
First, we calculate the discriminant \( b^2 - 4ac \):
\[ b^2 = (-6)^2 = 36 \] \[ 4ac = 4 \cdot 1 \cdot (-16) = -64 \] \[ b^2 - 4ac = 36 - (-64) = 36 + 64 = 100 \]
Now, we take the square root of the discriminant:
\[ \sqrt{100} = 10 \]
Now we can plug this back into the quadratic formula:
\[ x = \frac{-(-6) \pm 10}{2 \cdot 1} = \frac{6 \pm 10}{2} \]
This gives us two possible solutions for \( x \):
- \( x = \frac{6 + 10}{2} = \frac{16}{2} = 8 \)
- \( x = \frac{6 - 10}{2} = \frac{-4}{2} = -2 \)
Thus, the solutions are:
\[ x = 8, \quad x = -2 \]
The correct response is:
x equals 8, x equals negative 2.